2011
DOI: 10.1051/0004-6361/201117485
|View full text |Cite
|
Sign up to set email alerts
|

The formation of sunspot penumbra

Abstract: Aims. We study the magnetic flux emergence and formation of a sunspot penumbra in the active region NOAA 11024. Methods. We simultaneously observed the Stokes parameters of the photospheric iron lines at 1089.6 nm with the TIP and 617.3 nm with the GFPI spectropolarimeters along with broad-band images using G-band and Ca ii K filters at the German VTT. The photospheric magnetic field vector was reconstructed from an inversion of the measured Stokes profiles. Using the AZAM code, we converted the inclination fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 103 publications
6
58
1
Order By: Relevance
“…The penumbra forms in a bursty manner, with segments forming first on the outside of the developing sunspot, that is, away from the site of the magnetic flux emergence (Bray and Loughhead, 1964;Bumba, 1965b;Schlichenmaier et al, 2010). These first penumbral segments can be co-spatial with granular regions that become 'trapped' between emerging and merging magnetic fragments (Yang et al, 2003;Rezaei et al, 2012). The accumulation of magnetic flux as the emergence proceeds is clearly an important factor, with some work suggesting that there may be a critical flux value, Φ crit ≤ 5 × 10 20 Mx, which must be reached before the penumbra starts to form (Zwaan, 1987).…”
Section: Main Laws and Intrinsic Characteristics Of Large-scale Magnementioning
confidence: 99%
See 1 more Smart Citation
“…The penumbra forms in a bursty manner, with segments forming first on the outside of the developing sunspot, that is, away from the site of the magnetic flux emergence (Bray and Loughhead, 1964;Bumba, 1965b;Schlichenmaier et al, 2010). These first penumbral segments can be co-spatial with granular regions that become 'trapped' between emerging and merging magnetic fragments (Yang et al, 2003;Rezaei et al, 2012). The accumulation of magnetic flux as the emergence proceeds is clearly an important factor, with some work suggesting that there may be a critical flux value, Φ crit ≤ 5 × 10 20 Mx, which must be reached before the penumbra starts to form (Zwaan, 1987).…”
Section: Main Laws and Intrinsic Characteristics Of Large-scale Magnementioning
confidence: 99%
“…The accumulation of magnetic flux as the emergence proceeds is clearly an important factor, with some work suggesting that there may be a critical flux value, Φ crit ≤ 5 × 10 20 Mx, which must be reached before the penumbra starts to form (Zwaan, 1987). The magnetic field in the penumbra is highly inclined (≥ 60°, Rezaei et al, 2012) which suggests that as the magnetic flux in the sunspot increases due to flux emergence, so too does the inclination of the magnetic field to the vertical on the periphery of the sunspot.…”
Section: Main Laws and Intrinsic Characteristics Of Large-scale Magnementioning
confidence: 99%
“…Schlichenmaier et al (2010a,b) and Rezaei et al (2012) described the observational details and reported on the evolution of the AR, on the formation of the spot and on its magnetic properties.…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…The FPI observations were reconstructed with the Göttingen speckle code (de Boer 1996;Janssen 2003;Bello González et al 2007). The Stokes measurements were demodulated to yield the profiles (I λ , Q λ , U λ , V λ ) over the field of view (FOV) as described in Rezaei et al (2012).…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…We only used one node for all parameters except for the temperature (e.g., Beck 2008;Rezaei et al 2012). The magnetic field vector, the line-of-sight (LOS) velocity and temperature stratifications were retrieved from the inversion.…”
Section: Inversion Of Spectropolarimetric Datamentioning
confidence: 99%